Interrelationship between potassium rates and the efficiency of Bt genes in the control of Spodoptera frugiperda - Faria, Marcelo Macedo; Cintra, Pedro Henrique Nascimento; Amorim, Víctor Alves; Campos, Thiago Souza [UNESP]; Rocha, Ednaldo Cândido; Rodrigues, Fabricio (FapUNIFESP (SciELO), 2023)
The objective of this work was to identify the effect of potassium rates on Bt transgenic resistance and damage caused by Spodoptera frugiperda in corn plants at different developmental stages. The experimental design was a randomized complete block in a 3x6 factorial arrangement, with three potassium rates (0, 45, and 90 kg ha−1) and six corn hybrids (20A55Hx, 30A77PW, AG1051, MG652PW, NS90VTPro2, and NS92VTPro), with three replicates. The hybrids were evaluated through the analysis of canonical variables. With low potassium rates, the effectiveness of the corn hybrids in controlling the S. frugiperda caterpillar decreases in the different phenological stages. The use of the Bt technology is more efficient under an adequate potassium rate of 90 kg ha−1 KCl.
Inter-relação entre doses de potássio e a eficiência de genes Bt no controle de Spodoptera frugiperda
Keywords: caterpillar; damage; danos; lagarta; pest; praga; transgenics; transgênicos; Zea mays